Corticotropin-releasing hormone receptor subtypes in the rat anterior pituitary after two types of restraint stress - Klenerova, Vera; Sery, Omar; Hynie, Sixtus (Annals of the New York Academy of Sciences, 2008)
The stress response in anterior pituitary (AP) is mediated by corticotropin-releasing hormone (CRH) acting through CRH-R1 and -R2, however, the function of CRH-R2 in AP is still not fully elucidated. We used 1-h long restraint (IMO) as well as restraint combined with water immersion (IMO+C). Using real-time PCR we quantified mRNA expression of CRH-R1, CRH-R2alpha-soluble and -insoluble, and cAMP response element binding (CREB), with reference gene GAPDH. In control AP, CRH-R1 mRNA was up to 20-fold higher than levels of CRH-R2alpha-soluble or CRH-R2alpha-insoluble mRNA. IMO reduced CRH-R1 mRNA to 47% and 63% of control levels 1 and 2 h after the onset of stressor, respectively, while IMO+C did not produce significant changes. Our data demonstrated that these stressors did not change CRH-R2alpha mRNA, unlike the very significant response of CRH-R1 to IMO.
Keywords: Protein Isoforms; RNA, Messenger; Male; Receptors, Corticotropin-Releasing Hormone; Rats, Wistar; Corticotropin-Releasing Hormone; Restraint, Physical; protein vázající cAMP responzivní element; psychický stres; receptory hormonu uvolňujícího kortikotropin; Cyclic AMP Response Element-Binding Protein; mužské pohlaví; potkani Wistar; protein - isoformy; fyzické omezení; ponoření; adenohypofýza; krysa rodu Rattus; Animals; Immersion; Pituitary Gland, Anterior; zvířata; Stress, Psychological; hormon uvolňující kortikotropin; Rats; messenger RNA; CRF Receptor, Type 1; receptor CRF typu 1